Characterization of Oxygen and Ion Mass Transport Resistance in Fuel Cell Catalyst Layers in Gas Diffusion Electrode Setups - Lauf, Pascal; Lloret, Vicent; Geuß, Moritz; Cuadrado Collados, Carlos; Thommes, Matthias; Mayrhofer, Karl; Ehelebe, Konrad; Cherevko, Serhiy (Journal of The Electrochemical Society, 2023)
Fuel cell catalyst layers contain an essential active catalyst, a support material for electron conductivity, ionomer for proton conductivity, and porosity for gas transport, which build up complex interfaces that determine the overall performance. Subtle variations in the processing of the catalyst layers can significantly alter the performance, which demands intensive research efforts, and requires considerable amount of time. In the last few years, gas diffusion electrode (GDE) half-cell setups have been introduced as a promising approach to speed up catalyst layer evaluation. Yet, advanced methods to thoroughly characterize transport phenomena within the catalyst layer have not been established for GDE half-cell setups. In the present work, we adapt electrochemical characterization methods, such as O 2 transport resistance and CO-displacement, which have been previously developed for single cell testing, to enable unique insights into catalyst layers’ structure-performance relationships with the GDE method. Utilizing a commercial Pt/Vulcan catalyst as a test system, we identify the cause of mass transport limitations due to different ionomer contents. We show that an intermediate I/C ratio of 0.70, which forms a thin layer of ionomer, leads to an optimal performance for the Vulcan carbon support, due to an optimal compromise between O2 and proton accessibility.
CRIS-Team Scopus Importer:2023-07-21

Evaluating Electrocatalysts at Relevant Currents in a Half-Cell: The Impact of Pt Loading on Oxygen Reduction Reaction - Ehelebe, Konrad; Seeberger, Dominik; Paul, Mike T. Y.; Thiele, Simon; Mayrhofer, Karl; Cherevko, Serhiy (Journal of The Electrochemical Society, 2019)
In this work gas diffusion electrode (GDE) half-cells experiments are proposed as powerful tool in fuel cell catalyst layer evaluation as it is possible to transfer the advantages of fundamental methods like thin-film rotating disk electrode (TF-RDE) such as good comparability of results, dedicated elimination of undesired parameters etc. to relevant potential ranges for fuel cell applications without mass transport limitations. With the developed setup and electrochemical protocol, first experiments on different Pt/C loadings confirm excellent reproducibility. Thereby mass-specific current densities up to 30 A mg(Pt)(-1) at 0.6 V vs. RHE are achieved. From a methodological perspective, good comparability to single cell measurements is obtained after theoretical corrections for temperature and concentration effects. In comparison to previous studies with GDE half-cells, polarization curves without severe mass transport limitations are recorded in a broad potential window. All these achievements indicate that the proposed method can be an efficient tool to bridge the gap between TF-RDE and single cell experiments by providing fast and dedicated insights into the effects of catalyst layers on oxygen reduction reaction performance. This method will enable straightforward and efficient optimization of catalyst layer composition and structure, especially for novel catalysts, thereby contributing to the performance enhancements of fuel cells with reduced Pt loading. (c) The Author(s) 2019. Published by ECS. This is an open access article distributed under the terms of the Creative Commons Attribution 4.0 License (CC BY, http://creativecommons.org/licenses/by/4.0/), which permits unrestricted reuse of the work in any medium, provided the original work is properly cited. [DOI: 10.1149/2.0911915jes]
CRIS-Team WoS Importer:2019-12-13

Fuel cell catalyst layer evaluation using a gas diffusion electrode half-cell: Oxygen reduction reaction on Fe-N-C in alkaline media - Ehelebe, Konrad; Ashraf, Talal; Hager, Simon; Seeberger, Dominik; Thiele, Simon; Cherevko, Serhiy (Electrochemistry Communications, 2020)
Anion exchange membrane fuel cells (AEMFC) are a promising technology to allow the application of non-precious metal catalysts. While many of such catalysts have been identified in numerous recent fundamental research studies, reports evaluating these catalysts in realistic AEMFC catalyst layers together with stability assessments are rare. In the present work we show that fast and reliable evaluation and optimization of Fe-N-C-based oxygen reduction reaction (ORR) catalyst layers can be achieved using a gas diffusion electrode (GDE) half-cell approach. To set a benchmark in such measurements, a commercial Pajarito Powder Fe-N-C catalyst and commercial AemionTM ionomer are used. It is demonstrated that the ORR performance can be increased significantly by fine-tuning of the ionomer activation time. Furthermore, the optimized Fe-N-C-based catalyst layer shows very high stability with no observable performance deterioration after 5000 cycles in the 0.6–1.0 V vs. RHE potential window.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Alkaline fuel cell; Alkaline ionomer; Fe-N-C; Gas diffusion electrode; Non-noble metal catalyst; Oxygen reduction reaction

Graphene-Derived Carbon Support Boosts Proton Exchange Membrane Fuel Cell Catalyst Stability - Pavko, Luka; Gatalo, Matija; Finsgar, Matjaz; Ruiz-Zepeda, Francisco; Ehelebe, Konrad; Kaiser, Pascal; Geuß, Moritz; Dukic, Tina; Surca, Angelja Kjara; Sala, Martin; Bele, Marjan; Cherevko, Serhiy; et al. (ACS Catalysis, 2022)
The lack of efficient and durable proton exchange membrane fuel cell electrocatalysts for the oxygen reduction reaction is still restraining the present hydrogen technology. Graphene-based carbon materials have emerged as a potential solution to replace the existing carbon black (CB) supports; however, their potential was never fully exploited as a commercial solution because of their more demanding properties. Here, a unique and industrially scalable synthesis of platinum-based electrocatalysts on graphene derivative (GD) supports is presented. With an innovative approach, highly homogeneous as well as high metal loaded platinum-alloy (up to 60 wt %) intermetallic catalysts on GDs are achieved. Accelerated degradation tests show enhanced durability when compared to the CB-supported analogues including the commercial benchmark. Additionally, in combination with X-ray photoelectron spectroscopy Auger characterization and Raman spectroscopy, a clear connection between the sp(2) content and structural defects in carbon materials with the catalyst durability is observed. Advanced gas diffusion electrode results show that the GD-supported catalysts exhibit excellent mass activities and possess the properties necessary to reach high currents if utilized correctly. We show record-high peak power densities in comparison to the prior best literature on platinum-based GD-supported materials which is promising information for future application.
CRIS-Team WoS Importer:2022-08-26

Heating up the OER: Investigation of IrO2 OER Catalysts as Function of Potential and Temperature** - Czioska, Steffen; Ehelebe, Konrad; Geppert, Janis; Escalera-Lopez, Daniel; Boubnov, Alexey; Saraci, Erisa; Mayerhofer, Britta; Krewer, Ulrike; Cherevko, Serhiy; Grunwaldt, Jan-Dierk (ChemElectroChem, 2022)
Despite intensive investigations for unravelling the water splitting reaction, the catalyst behavior during the oxygen evolution reaction (OER) is still not fully understood. This is especially true under more demanding conditions like high potentials and high temperatures. Rotating disk electrode measurements show a gradual increase of OER current when increasing the temperature up to 80 °C. However, strong bubble formation at elevated temperatures makes in-situ characterization of the catalyst challenging. Here we utilize an in-situ electrochemical and heated flow cell, which aims at an efficient removal of bubbles from the catalyst surface and enables structural studies by X-ray absorption spectroscopy (XAS) at temperatures up to 80 °C. Changes in the Ir L3-edge X-ray absorption near edge spectra (XANES) were observed with respect to the white line position and principal components related to structural changes were extracted. At temperatures of 60 °C and above, the white line position of XANES spectra reaches a steady state, which is possibly caused by an equilibrium of different Ir oxidation states. These findings provide first spectroscopic insights in the behavior of OER catalysts at elevated temperatures which are typical for industrial applications and rarely addressed until now.
CRIS-Team Scopus Importer:2022-09-30
Keywords: electrochemistry; iridium oxide; oxygen evolution reaction; water splitting; X-ray absorption spectroscopy

Limitations of aqueous model systems in the stability assessment of electrocatalysts for oxygen reactions in fuel cell and electrolyzers - Ehelebe, Konrad; Escalera-Lopez, Daniel; Cherevko, Serhiy (Current Opinion in Electrochemistry, 2021)
Cost and stability remain the greatest technical barriers to sustainably commercialize low-temperature fuel cells and electrolyzers. For tackling this problem, numerous advanced electrocatalysts have been proposed and tested in aqueous model systems. There are, however, increasing and evident concerns regarding the value of stability data coming from such studies. Hence, we anticipate that finding new approaches to assess degradation will be a major undertaking in electrocatalysis research in the next years. Specifically, existing differences between fundamental and actual systems have to be addressed first: (a) electrode architecture; (b) electrolyte; (c) reactant and product transport; and (d) operating conditions. In this perspective, we discuss their influence on the stability of electrocatalysts using the challenging oxygen reduction and oxygen evolution reactions as illustrative cases.
CRIS-Team WoS Importer:2021-10-22

Platinum Dissolution in Realistic Fuel Cell Catalyst Layers - Ehelebe, Konrad; Knöppel, Julius; Bierling, Markus; Mayerhöfer, Britta; Böhm, Thomas; Kulyk, Nadiia; Thiele, Simon; Mayrhofer, Karl; Cherevko, Serhiy (Angewandte Chemie International Edition, 2021)
Pt dissolution has already been intensively studied in aqueous model systems and many mechanistic insights have been gained. Nevertheless, transfer of new knowledge to real-world fuel cell systems is still a significant challenge. To close this gap, we present a novel in situ method combining a gas diffusion electrode (GDE) half-cell with inductively coupled plasma mass spectrometry (ICP-MS). With this setup, Pt dissolution in realistic catalyst layers and the transport of dissolved Pt species through Nafion membranes were evaluated directly. We observed that 1) specific Pt dissolution increased significantly with decreasing Pt loading, 2) in comparison to experiments on aqueous model systems with flow cells, the measured dissolution in GDE experiments was considerably lower, and 3) by adding a membrane onto the catalyst layer, Pt dissolution was reduced even further. All these phenomena are attributed to the varying mass transport conditions of dissolved Pt species, influencing re-deposition and equilibrium potential.
CRIS-Team WoS Importer:2021-03-12